Desentralisasi Pemerintah Pusat dan Pemerintah Kabupaten Malang dalam Upaya Pemberantasan Rokok Tanpa Cukai - Budiman, Muhammad Raihan; Dziki Zainal Arifin, Muhammad; Fatulloh, Yunus; Hendra, Hendra (LPPM Universitas Ekasakti Padang, 2024)
Increasing tobacco control has been mandated as part of Indonesia's 2020-2024 National Medium-Term Development Plan (RPJMN), because Indonesia is currently one of the countries with the highest prevalence of smoking. On the other hand, Indonesia's position as one of the largest tobacco producers requires an appropriate reduction strategy, particularly in relation to the illicit tobacco trade. Therefore, a solid and sufficient intrasectoral collaboration strategy needs to be identified. Malang Regency was chosen as the focus area in this study to study collaborative governance policies between the central and local governments in the form of decentralization in order to provide coping strategies in combating the illegal tobacco trade.